Are Hypomineralized Primary Molars and Canines Associated with Molar-Incisor Hypomineralization? - Silva Figueiredo Se, Maria Jose da; Dias Ribeiro, Ana Paula; Martins dos Santos-Pinto, Lourdes Aparecida [UNESP]; Loiola Cordeiro, Rita de Cassia [UNESP]; Cabral, Renata Nunes; Leal, Soraya Coelho (Amer Acad Pediatric Dentistry, 2017)
Purpose: The purpose of this study was to evaluate the prevalence of and relationship between hypomineralized second primary molars (HSPM) and hypomineralized primary canines (HPC) with molar-incisor hypomineralization (MIH) in 1,963 schoolchildren. Methods: The European Academy of Paediatric Dentistry (EAPD) criterion was used for scoring HSPM/HPC and MIH. Only children with four permanent first molars and eight incisors were considered in calculating MIH prevalence (n equals 858); for HSPM/HPC prevalence, only children with four primary second molars (n equals 1,590) and four primary canines (n equals 1,442) were considered. To evaluate the relationship between MIH/HSPM, only children meeting both criteria cited were considered (n equals 534), as was true of MIH/HPC (n equals 408) and HSPM/HPC (n equals 360; chi-square test and logistic regression). Results: The prevalence of MIH was 14.69 percent (126 of 858 children). For HSPM and HPC, the prevalence was 6.48 percent (103 of 1,592) and 2.22 percent (32 of 1,442), respectively. A significant relationship was observed between MIH and both HSPM/HPC (P<0.001). The odds ratio for MIH based on HSPM was 6.31 (95 percent confidence interval [CI] equals 2.59 to 15.13) and for HPC was 6.02 (95 percent CI equals 1.08 to 33.05). Conclusion: The results led to the conclusion that both hypomineralized second primary molars and hypomin-eralized primary canines are associated with molar-incisor hypomineralization, because children with HSPM/HPC are six times more likely to develop MIH.
Keywords: TOOTH DEMINERALIZATION; CHILD; ORAL HEALTH; DECIDUOUS TOOTH